2010
DOI: 10.1038/onc.2009.433
|View full text |Cite
|
Sign up to set email alerts
|

ERα signaling through slug regulates E-cadherin and EMT

Abstract: The ERa signaling pathway is one of the most important and most studied pathways in human breast cancer, yet numerous questions still exist such as how hormonally responsive cancers progress to a more aggressive and hormonally independent phenotype. We have noted that human breast cancers exhibit a strong direct correlation between ERa and E-cadherin expression by immunohistochemistry, suggesting that ERa signaling might regulate E-cadherin and implying that this regulation might influence epithelial-mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 48 publications
11
135
0
3
Order By: Relevance
“…In recent years, epithelial-mesenchymal transition (EMT) has been recognized as a key step during the progression of primary tumors into metastases as well as its original role during embryogenesis (31,32). ERα signaling through Slug regulates E-cadherin and EMT (33). In our study, consistent decrease of both the epithelial marker and ERα suggested EMT features, which could explain the acquisitions of tumorigenesis and invasive capacity.…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, epithelial-mesenchymal transition (EMT) has been recognized as a key step during the progression of primary tumors into metastases as well as its original role during embryogenesis (31,32). ERα signaling through Slug regulates E-cadherin and EMT (33). In our study, consistent decrease of both the epithelial marker and ERα suggested EMT features, which could explain the acquisitions of tumorigenesis and invasive capacity.…”
Section: Discussionmentioning
confidence: 67%
“…CK expression in triple-negative tumor CTCs requires additional study and a larger sample population. Expression of PR indicates a functional ERα (one of the two isoforms of ER) and ERα pathway (23), which increases E-cadherin expression by downregulating transcriptional repressors (24,25). Patients with Her2-positive tumors lack ER and PR expression, which decreases the level of E-cadherin, and enhances the possibility of EMT and tumor cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have shown that ERα and FOXA1 are involved in E-cadherin expression, 20,21) we investigated the genes important for E-cadherin expression in breast cancer cells by stable expression of each gene in MDA-MB-231 cells. Although E-cadherin expression was profoundly induced at the mRNA and protein levels by stable expression of FOXA1, ERα expression did not affect E-cadherin expression (Figs.…”
Section: Foxa1 Induces E-cadherin Expression Independently Of Erαmentioning
confidence: 99%